Green Innovation in MSMEs: Adaptive Strategies for Competitiveness and Sustainable Economic Growth - Sabil, Sabil; Hakim, Lukman; Lestiningsih, Amin Setio; Widodo, Dwiyatmoko Puji; Sugiyah, Sugiyah; Sofyanty, Devy (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study examines green innovation and adaptive strategies as strategic determinants of MSME competitiveness and sustainability in the context of sustainable economic development. It analyzes how green innovation contributes to sustainable economic growth and identifies key drivers and barriers to its implementation, while also assessing the role of adaptive strategies in responding to globalization, shifting consumer preferences, and rising environmental demands. Using a quantitative survey of 150 MSMEs in Indonesia and data analysis with PLS-SEM, the study tests the relationships among green innovation, adaptive strategies, competitiveness, and sustainable economic growth. The results show that green innovation significantly promotes sustainable economic growth, and adaptive strategies are crucial in enhancing MSME competitiveness as well as mediating the relationship between green innovation and economic growth. Nonetheless, limited resources, constrained technological access, and weak regulatory support remain major obstacles. Theoretically, the study advances the literature on the integration of green innovation and adaptive strategies in MSMEs in developing countries. Practically, it offers implications for policy and managerial strategies to strengthen MSME competitiveness and sustainability through multi-stakeholder collaboration and policy incentives.